Interaction between gut microbiota and immune checkpoint inhibitor-related colitis - Zhou, Guanzhou; Zhang, Nana; Meng, Ke; Pan, Fei (Frontiers in Immunology, 2022)
Immune checkpoint inhibitors (ICIs) have become a promising therapeutic strategy for malignant tumors, improving patient prognosis, along with a spectrum of immune-related adverse events (irAEs), including gastrointestinal toxicity, ICI-related colitis (IRC), and diarrhea. The gut microbiota has been suggested as an important regulator of the pathogenesis of IRC, and microbiota modulations like probiotics and fecal microbiota transplantation have been explored to treat the disease. This review discusses the interaction between the gut microbiota and IRC, focusing on the potential pathogenic mechanisms and promising interventions.